A comparative study of antifungal activity of Lavender brew, Lavender essential Oil, and Clotrimazole: an in vitro study - Fereshteh Behmanesh; Hajar Pasha; Seyyed Ali Asghar Sefidgar; Aliakbar Moghadamnia; Zahra Basirat (Babol University of Medical Sciences, 2015)
Introduction: Vaginal yeast infections (candidiasis) are among the most common gynecologic infections in women. Due to the high prevalence of vaginal candidiasis and its recurrence, followed by such chemical treatment as Clotrimazole, this study was performed with the broad aim of comparing the in vitro effects of Lavender brew, Lavender essential oil, and Clotrimazole on the growth of the standard strains of Candida albicans.  Methods: The fungus cell count was done through Thoma counting chambers and Hemocytometer slide. Having prepared the dilution (6 × 106 of standard Candida albicans, S.C.a-PTCC-2657) in the Sabouraud Agar liquid medium, the essential oil and brew of Lavandula angustifolia and Clotrimazole were added to different dilutions (½ , ¼ , ⅛) (in 4 stages) before the fungus cell count was done. Having obtained the necessary information, the data were analyzed through Statistical Package for the Social Sciences (SPSS), and a general linear model was used for the analysis of the data. The test results were then compared.  Results: The number of fungi cells in Lavender brew (14 × 106) and Lavender essential oil (35× 106) decreased significantly compared with those of Clotrimazole (93 × 106) and fungus control (188 × 106) (p<0.01). Also, the fungus cell count in dilutions of ½ and ¼ of the drugs in the brew, and in dilutions of ⅛ in essential oil were less than those of other proportions. The highest antifungal efficacies of the drugs were observed in higher dilution (p< 0.01), and Clotrimazole had the least antifungal effect. Conclusion: Lavender brew and Lavender essential oil had more antifungal effect on the standard Candida albicans when compared with Clotrimazole.